A naturally occurring promoter variation of BrGSL-OHa contributes to the conversion of gluconapin to progoitrin in Brassica rapa L. leaves - Zheng, Jingyi; Choi, Su Ryun; Jing, Yue; Zhang, Wenjun; Sun, Yan; Li, Xiaonan; Lim, Yong Pyo (Frontiers in Plant Science, 2025)
Glucosinolates (GSLs) are sulfur-rich secondary metabolites that play important roles in human health, plant defenses against pathogens and insects, and flavor. The genetic architecture of GSL biosynthesis in Brassica rapa L. remains poorly understood despite several mapping and gene prediction studies. This study conducted a conventional quantitative trait locus (QTL) analysis to identify putative genes regulating GSL biosynthesis in B. rapa in two field trials. Four consensus QTL clusters were identified for various GSL compounds. Six QTLs exhibited effects of QTL–environment interactions (Q×E), reflecting the genetic variation underlying phenotypic plasticity. QTL-Cluster2 and QTL-Cluster3 on chromosome A03 represented two genetically stable regions for major aliphatic GSLs (Ali-GSLs) without Q×E effects. Interestingly, variation in the expression of BrGSL-OHa, rather than gene sequence variation, explained the association between QTL-Cluster2 and gluconapin and progoitrin accumulation in B. rapa. Further function analysis indicated that the lack of an MYB binding site in the oil-type B. rapa BrGSL-OHa promoter region represented a rare non-functional allele among B. rapa genotypes, which prevented binding with the MYB transcription factor BrMYB29b, thereby repressing BrGSL-OHa transcription and inhibiting progoitrin biosynthesis. This study provides new insights regarding the molecular regulatory mechanism of GSL biosynthesis in B. rapa.